Strategi Penerapan Contextual Teaching and Learning (CTL) Dalam Pembelajaran Pendidikan Agama Islam - Sri Afrianita Lasumbu; Dissa Pontoh; Moh. Fandry Yunus; Sitti Nur Alysah Mokoginta; Pebriani Gumohung; Ridwanto Djahuno (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
This study aims to analyze the strategy of implementing Contextual Teaching and Learning (CTL) in Islamic Religious Education learning at SDN 2 Dalapuli, describe the implementation of CTL components in the learning process, and explain the importance of implementing CTL in supporting meaningful learning. This study uses a qualitative approach with a descriptive type. Data is collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the strategy of implementing CTL is carried out through associating the material with the student's real life context, using contextual questions, providing concrete examples, modeling, and reflection. The implementation of the dominant CTL components includes constructivism, questioning, modeling, and reflection, while the components of inquiry, learning community, and authentic assessment have not been optimally applied. The application of CTL in Islamic Religious Education learning at SDN 2 Dalapuli has helped create more contextual, active, and meaningful learning for students. Thus, the CTL implementation strategy needs to continue to be strengthened so that all components of contextual learning can be carried out more completely and systematically.